3D Printing of Black Bioceramic Scaffolds with Micro/Nanostructure for Bone Tumor‐Induced Tissue Therapy. Issue 21 (15th September 2021) - Wang, Xin; Liu, Yin; Zhang, Meng; Zhai, Dong; Wang, Yufeng; Zhuang, Hui; Ma, Bing; Qu, Yu; Yu, Xiaopeng; Ma, Jingge; Ma, Hongshi; Yao, Qingqiang; et al.
Abstract: It is common to improve the relevant performance in the field of energy storage materials or catalytic materials by regulating the number of defects. However, there are few studies on the biomaterials containing defects for tissue engineering. Herein, a new type of defect‐rich scaffolds, black akermanite (B‐AKT) bioceramic scaffolds with micro/nanostructure, the thickness of which is from 0.14 to 1.94 µm, is fabricated through introducing defects on the surface of bioceramic scaffolds. The B‐AKT scaffolds have advantages on the degradation rate and the osteogenic capacity over the AKT (Ca2 MgSi2 O7 ) scaffolds due to the surface defects which stimulate the osteogenic differentiation of rabbit bone mesenchymal stem cells via activating bone morphogenetic protein 2 （BMP2） signaling pathway and further promote bone formation in vivo. In addition, the prepared B‐AKT scaffolds, the temperature of which can be over 100 °C under the near infrared （NIR） irradiation (0.66 W cm −2 ), possess excellent performance on photothermal and antitumor effects. The work develops an introducing‐defect strategy for regulating the biological performance of bioceramic scaffolds, which is expected to be applied in the next generation of bioceramic scaffolds for regenerative medicine. Abstract : This work develops a new modification strategy, introducing defects, to endow black akermanite (B‐AKT) bioceramic scaffolds with satisfactory physicochemical and biological properties, such as homogeneous surface micro/nanostructure, controlled degradation performance, noticeable osteogenic capacity and excellent photothermal tumor therapy effects, which is expected to provide inspiration for the development of bioceramics in the bone tumor‐induced tissue therapy application.